Economic Empowerment of Waqf Assets in Muhammadiyah Model - Uus Putria; M. Yusuf Wibisono (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the role of organizational culture in managing productive waqf at Muhammadiyah Sukajadi Bandung and its implications for socio-economic empowerment. The key concepts include productive waqf, organizational culture, nazhir, and progressive Islam. The research employs a qualitative case study design, utilizing in-depth interviews, participant observation, and document analysis. The object of the study is the management of waqf assets in Muhammadiyah Sukajadi Bandung, particularly in education, business, and health sectors. The main findings reveal that the success of productive waqf is strongly supported by an organizational culture that emphasizes sincerity, professionalism, transparency, and ideological commitment, enabling waqf to function as a sustainable social investment instrument. The major challenges include limited managerial capacity of some nazhir, resistance to innovation, and public perceptions of waqf as a static asset. Practical recommendations highlight the importance of strengthening Islamic economic literacy, professional training for waqf managers, and developing innovative waqf models. This study contributes to Islamic economic theory and organizational sociology by proposing a conceptual framework of religious organizational culture as symbolic social capital in productive waqf governance.